FORMATION OF AN ENTREPRENEUR MINDSET IN CREATING COMPETITIVENESS OF FEMALE ENTREPRENEURS - Librina Tria Putri; Rahmawati Rahmawati; Dwika Lodia Putri (International Journal of Social Science, 2022)
Purpose - The purpose of this paper is to understand the formation of an entrepreneur mindset in creating the competitiveness of female entrepreneurs Design/methodology/approach – The literature review approach is an assessment and critical review of knowledge, ideas, or findings contained in the body of a literature. Findings – The problems faced in the development of Female Entrepreneurs are the entrepreneurial culture that exists in an area that can limit a woman to be creative, the entrepreneurial spirit has not been optimally developed, and personal skills in communication are still relatively low. The emergence of e-commerce as a breakthrough for business people engaged in the creative industry makes female entrepreneurs have to learn more about mastering technology, so that they have the potential to expand opportunities for further development, and can create competitive advantages that are built on the principle of identifying opportunities, innovation, acceptance of risk, flexibility in responding to change, building a clear vision and growth in creativity and innovation. Research limitations/implications – The limitations of writing this paper are shortcomings in article collection, there are still other articles that have not been included in this paper. Practical implications – The results of this literature review will help women entrepreneurs explore their potential and be able to control themselves in running the business they are engaged in. Social implications – Female Entrepreneurs need to get attention from their environment because women also have a big role in advancing the economy of a country. Originality/value – in this paper is the importance of e-commerce in business management as a transaction system, because it will increase market exposure so as to create competitiveness